(untitled) (The International Research Journal of Management Science, 2024)
Purpose: As organizations increasingly emphasize sustainability, understanding how leadership styles affect employee engagement becomes crucial. This research aims to analyze the effect of transformational leadership on employee commitment to sustainable practices, highlighting the mediating role of occupational delight. Methodology: This study adopted a causal-comparative research design and a quantitative approach. It collected data from bank employees with different job responsibilities and analyzed it using descriptive and inferential statistics following the PROCESS Macro. Findings: This study posits that transformational leadership enhances employee commitment to sustainable work practices towards sustainability by fostering occupational delight. The findings suggest that creating a work environment that promotes fulfillment can significantly contribute to sustainability practices. Originality/Value: This study concludes that effective leadership is essential for employees’ commitment and that leaders should follow transformational leadership. Further, the study integrated occupational delight into the relationship between transformational leadership and employees’ commitment to sustainable work practices. Implications: The study’s findings and conclusion will help organizations develop a strategic leadership approach in the competitive business environment.